The interconnection of mountain and lowland landscapes in historical perspective - Renes, H. (TÁJÖKOLÓGIAI LAPOK, 2018)
Most historic landscape research takes place within individual countries or even regions. However, landscapes and regions have always been interconnected and we cannot understand any landscape without taking their connections into account. This is certainly the case with mountain landscapes, which were often framed as remote, isolated and self-supporting, but in reality were always connected to the outside world. Exchange with lowland regions existed in different forms: in transhumance systems, in specialised forms of agriculture and in specific products. Over the long run, the resilience of mountain landscapes was not connected to stability, but to creative adaptation to ever changing eternal conditions.